The effect of green economy increasing green entrepreneuship interest in Indonesia - Chairia, Chairia; Yanti, Aprilda; Cahyati, Suci (Trigin Publisher, 2024)
Green entrepreneurship involves addressing environmental issues and making a positive impact, such as the use of environmentally friendly raw materials, clean manufacturing processes, waste management and recycling, etc. These different understandings make a positive contribution to environmental protection and thus serve as a problem-solving mechanism to achieve the SDGs. Its implementation requires educational support and collaboration with stakeholders. The method used in this research is a literature study. The data obtained is compiled, analyzed and concluded. So as to get a conclusion about the literature study. These findings can be an effective step for educators in improving students' understanding of green entrepreneurship and have a positive judgement about being a green entrepreneur. Universities and families should also actively actively seek to instil relevant values for students such as altruism through the provision of practical environmental training. Such practices are are useful to stimulate students' intention to become active entrepreneurs in a sustainable manner and improve environmental performance.